Clueless [videorecording (DVD)] - Heckerling, Amy; Silverstone, Alicia; Rudd, Paul; Dash, Stacey; Murphy, Brittany; Hedaya, Dan; Sisto, Jeremy, 1974-; Meyer, Breckin, 1974-; Walker, Justin (Actor); Shawn, Wallace; Caplan, Twink; Brown, Julie, 1958-; et al. (Widescreen DVD collection., 2005)
15-year-old Cher, the matchmaking Beverly Hills High schooler, has shopping and boys on her mind. She leads a hectic lifestyle but keeps it all together until she starts to fall in love and finds she's 'clueless'. A loose adaptation of Emma, Jane Austen's 19th-century comedy of manners.